2018
DOI: 10.1002/jsfa.9347
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids retention in biofortified yellow cassava processed with traditional African methods

Abstract: The results indicated that biofortified boiled cassava could be an effective food product to improve pVACs intake in areas where vitamin A deficiency exists, and processing of chikwangue and fufu should be improved before promoting biofortified cassava in vitamin-A-deficient areas with high cassava consumption. © 2018 The Authors. Journal of the Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 22 publications
4
20
1
Order By: Relevance
“…This, therefore, implies that extensive processing may be a hindrance in the utilization of these new crops. High depletion of β-carotene levels after cooking was similarly observed from reported literature [40]. Even though the impact of consuming gari and its dough on vitamin A serum concentrations is not yet fully established in VAD populations, the results presented give a hint that the newly released varieties of Cassava have a chance of reducing the burden of VAD in sub-Saharan populations where it is still endemic.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…This, therefore, implies that extensive processing may be a hindrance in the utilization of these new crops. High depletion of β-carotene levels after cooking was similarly observed from reported literature [40]. Even though the impact of consuming gari and its dough on vitamin A serum concentrations is not yet fully established in VAD populations, the results presented give a hint that the newly released varieties of Cassava have a chance of reducing the burden of VAD in sub-Saharan populations where it is still endemic.…”
Section: Resultssupporting
confidence: 79%
“…These observed losses could also be due to carotenoids isomerization and oxidation which is the breakdown of trans-carotenoids to their cis isomers due to increased contact with moisture, heat treatment, and exposure to light [38,39]. More recent findings confirm these depletion patterns in Cassava products consumed in Sub-Saharan Africa [21,40].…”
Section: Resultsmentioning
confidence: 88%
“…Currently, the biofortified cassava program conventionally breeds for pVACS with breeding targets set for 15 μg/g. A recent retention study showed great losses of pVACs during processing and cooking of two primary forms of cassava consumed, fufu and chikwangwe, with a mere~2% and~10% of pVACS remaining, respectively [29]. These large losses in pVACs are in part a result of the large losses of solid mass due to the processing, with primary cassava products fufu and chikwangwe containing about one-quarter to one-third of solid mass of the cassava cubes after processing.…”
Section: South Kivumentioning
confidence: 99%
“…The processing significantly causes carotenoid content loss in cassava products, 10 , 11 from 10–20% in wet paste fufu up to 50–70% in roasted products such as gari, chikwangue and pupuru. 12 , 13 , 14 Other interventions are thus required to make up for the post‐processing losses and improve the nutritional value of yellow cassava food products. 15 New foods from micronutrient‐rich leafy vegetables (vitamin A, iron and zinc) and cassava would improve a starch‐based diet's nutrient value.…”
Section: Introductionmentioning
confidence: 99%